Racial Disparities Exist in Surgical Outcomes for Patients with Inflammatory Bowel Disease (IBD) - Dos Santos Marques, Isabel C. (Am J Surg, 2018)
BACKGROUND: Racial disparities in surgical outcomes exist for Black patients with IBD compared to White patients. However, previous studies fail to include other racial/ethnic populations. We hypothesized these disparities exist for Hispanic and Asian patients. METHODS: This is a retrospective cohort study of patients undergoing surgery for IBD using the American College of Surgeons National Surgical Quality Improvement Program (ACS- NSQIP) database (2005–2017). Bivariate comparisons and adjusted multivariable regressions were performed to evaluate associations between race and outcomes. RESULTS: Of 23,901 patients with IBD, the racial/ethnic makeup were: 88.7% White, 7.6% Black, 2.4% Hispanic and 1.4% Asian. Overall mean LOS was 8 days (SD 8.2) and significantly varied between groups (8d for White, 10d for Black, 8.5d for Hispanic, and 11.1d for Asian; p<0.001). Hispanic patients had the highest odds of readmission (OR: 1.4; 95% CI 1.1–1.8). Black patients had increased odds of renal insufficiency (OR: 1.8; 95% CI 1.1–2.9), bleeding requiring transfusions (OR: 1.7; 95% CI 1.4–1.9), and sepsis (OR: 1.7; 95% CI 1.4–2.02) compared to White patients. CONCLUSIONS: Racial disparities exist among IBD patients undergoing surgery. Black, Hispanic and Asian IBD patients experience major disparities in post-operative complications, readmissions and LOS, respectively, when compared to White patients with IBD. Future research is needed to better understand the mechanisms of these disparities including evaluation of social determinants of health.